Valuation of Phoenics - Köppl, Stefan (2014)
This work presents theoretical background for diverse valuation methods, with special attention paid to the real options method and its advantages over traditional methods for valuation of young entities. Additionally, it presents a case study of a start-up company, the value of which is found using diverse methods. The main result shows that the value of the company obtained with the real options approach is much higher than the one found with traditional discounted cash flow (DCF) method. Moreover, it shows that the difference in the obtained valuations leads to different strategic decisions: according to DCF certain projects should not be undertaken, whereas according to the real options approach the company should expand its operations.